Expressão dos genes VEGFA e NFE2L2 e regulação por microRNAs em câncer papilífero de tireoide - Stuchi, Leonardo Prado (2017)
Colloid goiter and papillary thyroid cancer are the most common alterations of the thyroid gland. Angiogenesis and oxidative stress play key roles in the progression of cancer, especially the genes VEGFA and NFE2L2, involved in these processes. Gene expression can be regulated by microRNAs (miRNAs, miR), a class of gene regulators that controls cellular processes such as cell growth, differentiation, proliferation, and apoptosis. Hsa-miR-17-5p and hsa-miR-612 are possible regulators of the VEGFA and NFE2L2 genes and may participate in the processes that result in cellular changes in the thyroid and development of disorders such as colloid goiter and papillary cancer. Objectives: To evaluate the gene and protein expression of VEGFA and NFE2L2 and expression of hsa-miR-17-5p and hsa-miR-612 in human papillary thyroid, colloid goiter and normal thyroid tissue samples. Moreover, to investigate the involvement of hsa-miR-17-5p and hsa-miR-612 in the regulation of VEGFA and NFE2L2 genes using thyroid papillary cancer cell line (TPC-1 strain). Materials and Methods: Fifteen samples of papillary thyroid cancer, 15 colloid goiter and their respective adjacent tissues, and six samples of normal thyroid tissue were included in the study. The genes and miRs` analysis were performed using the quantitative real-time PCR technique (qPCR). The quantification of the VEGFA protein was performed using the enzyme-linked immunosorbent assay (ELISA), and the expression of NFE2L2 protein was evaluated by the immunohistochemistry technique. The TPC-1 cell line was transfected with the miR-17-5p inhibitor and the miR-612 mimic in order to evaluate the gene regulation by miRs; the expression of the VEGFA and NFE2L2 genes was quantified by qPCR. Results: The VEGFA gene presented high expression in the tumor and its adjacent tissue (P = 0.0125 and P = 0.0023, respectively) and goiter and adjacent tissue (P <0.0001 for both tissues) compared to normal tissue, as well as the gene NFE2L2 (tumor: P = 0.0061 and adjacent: P = 0.0149; goiter: P = 0.0009 and adjacent: P <0.0001). Gene expression of VEGFA was higher in the goiter than in the tumor (P <0.0001) and adjacent tissues (P <0.0001). Hsa-miR-612 showed reduced expression in adjacent tumor tissue (P = 0.016), goiter and tissue adjacent to goiter (P = 0.015, P = 0.0131, respectively). Hsa-miR-17-5p showed reduced expression only in goiter and its adjacent tissue (P <0.0001; P = 0.0448, respectively). Hsa-miR-17-5p was more expressed in the tumor than in the goiter (P = 0.033). Negative correlation was observed between expression of hsa-miR-612 and expression of VEGFA and NFE2L2 in the tumor (P = 0.038, P = 0.007) and in the goiter with NFE2L2 (P = 0.002). Expression of miR-17-5p was negatively correlated to NFE2L2 gene in the tumor (p = 0.019). Protein quantification of VEGFA was increased in papillary cancer, adjacent tissue and goiter (P = 0.0009, P = 0.0138, P = 0.0397, respectively) compared to normal tissue The tumor showed higher expression. of the VEGFA protein in relation to goiter and its adjacent tissue (P = 0.022, P = 0.0003). The quantification analysis of the Nrf2 protein showed higher expression in the tumor`s cytoplasm in relation to goiter (P <0.0001) and normal tissue (P <0.0001). The tumor also presented an increased Nrf2 expression in relation to goiter (P <0.0001) in the nucleus. Transfection of the miR-17-5p inhibitor into the TPC-1 cell line resulted in inhibition of NFE2L2 gene expression by approximately 73%. Conclusion: The NFE2L2 and VEGFA genes and their protein products are widely expressed in papillary thyroid cancer and colloid goiter. Hsa-miR-612 has differential expression in the thyroid tumor and colloid goiter, and hsa-miR-17-5p has differential expression only in colloid goiter . Hsa-miR-17-5p positively regulates expression of the NFE2L2 gene in papillary thyroid cancer. Hsa-mir-612 does not participate in the regulation of VEGFA and NFE2L2 gene expression in this tumor type.